The Protective Effect of Metformin Against Testicular Damage in Diabetes and Prostate Cancer Model - Aydın, Pınar Köroğlu; Karabulut-Bulan, Ömür; Bugan, İlknur; Türkyılmaz, İsmet Burcu; ALTUN, SEYHAN; Yanardağ, Refiye (Wiley, 2022)
Individuals with diabetes have an increased risk of breast, colorectal, pancreatic and prostate cancer. Metformin, an oral biguanide used to treat diabetes, has anti-hyperglycaemic, anti-hyperinsulinemic and antioxidant activities. The effects of metformin on testicular tissue damage in cancer and diabetic + cancer rat models were evaluated histologically, immunohistochemically and biochemically. The diabetic model was produced in Copenhagen rats using a single dose of streptozotocin (65 mg/kg), while prostate cancer was induced through subcutaneous inoculation of 2 x 10(4) Mat-LyLu cells into the animals. At the end of the experimental period, testicular tissues with a close functional relationship to the prostate were collected. Histological evaluation found moderate to severe damage to testes following the diabetes and cancer process. Histopathological and biochemical impairments were observed in the early stage of prostate cancer, which were increased in the diabetic animals. Metformin administration reversed these injuries and provided substantial protection of the testes. In particular, metformin had protective effects on tissue damage, apoptosis, oxidative stress and antioxidant capacity. This suggests that metformin should be further investigated as a targeted protective drug against prostate cancer-related damage to the testes.
Keywords: Diabetes; Metformin; Oxidative Stress; Prostate Cancer; Testicular Damage